DETERMINAN FRAUDULENT FINANCIAL REPORTING DENGAN MEKANISME CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Sofiani Retnoningtyas; M Irfan Tarmizi (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to analyze the determinants of risk factors for financial reporting fraud, which are proxied based on financial targets, ineffective monitoring, director turnover, and auditor turnover moderated by corporate governance mechanisms. Sample selection using purposive sampling method. The total population in this study was 46. The sample of this study was 81 banking companies listed on the IDX in the 2019-2021 period. This study tested the hypothesis in multivariate analysis using logistic regression with Eviews-9. The results of this study found that the board of commissioners, independent commissioners, and institutional ownership were significantly unable to moderate the relationship between fraud diamond determinants and fraudulent financial reporting. Meanwhile, the audit committee was able to moderate the relationship between institutional ownership and fraudulent financial reporting.